Adhesion properties of potentially probiotic Lactobacillus kefiri to gastrointestinal mucus - Carasi, Paula (2014)
We investigated the mucus-binding properties of aggregating and non-aggregating potentially probiotic strains of kefir-isolated Lactobacillus kefiri, using different substrates. All the strains were able to adhere to commercial gastric mucin (MUCIN) and extracted mucus from small intestine (SIM) and colon (CM). The extraction of surface proteins from bacteria using LiCl or NaOH significantly reduced the adhesion of three selected strains (CIDCA 8348, CIDCA 83115 and JCM 5818); although a significant proportion (up to 50%) of S-layer proteins were not completely eliminated after treatments. The surface (S-layer) protein extracts from all the strains of Lb. kefiri were capable of binding to MUCIN, SIM or CM, and no differences were observed among them. The addition of their own surface protein extract increased adhesion of CIDCA 8348 and 83115 to MUCIN and SIM, meanwhile no changes in adhesion were observed for JCM 5818. None of the seven sugars tested had the ability to inhibit the adhesion of whole bacteria to the three mucus extracts. Noteworthy, the degree of bacterial adhesion reached in the presence of their own surface protein (S-layer) extract decreased to basal levels in the presence of some sugars, suggesting an interaction between the added sugar and the surface proteins. In conclusion, the ability of these food-isolated bacteria to adhere to gastrointestinal mucus becomes an essential issue regarding the biotechnological potentiality of Lb. kefiri for the food industry.